If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 = 2(l + l + -1w) Combine like terms: l + l = 2l 72 = 2(2l + -1w) 72 = (2l * 2 + -1w * 2) 72 = (4l + -2w) Solving 72 = 4l + -2w Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4l' to each side of the equation. 72 + -4l = 4l + -4l + -2w Combine like terms: 4l + -4l = 0 72 + -4l = 0 + -2w 72 + -4l = -2w Add '-72' to each side of the equation. 72 + -72 + -4l = -72 + -2w Combine like terms: 72 + -72 = 0 0 + -4l = -72 + -2w -4l = -72 + -2w Divide each side by '-4'. l = 18 + 0.5w Simplifying l = 18 + 0.5w
| 6n^2+11n-95=0 | | 180-3x=6x | | .4x+.7y=.5*20 | | 3m+7(m+7)=89 | | 2n^2+2=10n | | 4c^3-1c=0 | | 9-16+6x=11x+4x-5 | | 4u+5u+4u=p+q | | 3x^2-21x^6=0 | | Y-1=4y-10 | | 3(-5)+2=5 | | X^2-5p=0 | | 2x^4+5x^2-12=0 | | 5/8-(5/6) | | 17x^2-12xy+8y^2-22x-4y+14=0 | | 3(x+y)-r=2y | | B^2-2b+7=0 | | 2z=14-20 | | 4x-30+3x=180 | | 12x-14=70+9x | | X-1/6=23/6 | | y(n)-0.5y(n-1)=x(n)+x(n-1) | | -54-17x=90-14x | | 12x-14=50+9x | | (x^4/8)^3 | | 108-2x=4y | | 2y+3=-3y-7 | | m^2+16m+4=0 | | P+4t=9t | | 1-10n+9n-1= | | (4x^2)+6x=5 | | a(n-2)+3=bn |